The dynamics of human communication : a laboratory approach - Myers, Gail E; Myers, Michele Tolela (McGraw-Hill, 1988)
Designed for the first course in interpersonal communication, the Sixth Edition retains the features that have contributed to its long-standing success: a clear, conversational writing style; and the self-contained Lab Manual that includes case studies, exercises, and examples which link principles and practices in an experiential environment.
Keywords: behaviorální vědy; psychologie, klinická psychologie; Behavioral Sciences; Psychology, Social; sociální psychologie